2003
DOI: 10.1016/s1470-0328(02)02675-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective termination of a twin pregnancy as a treatment of severe pre-eclampsia

Abstract: Case reportA 32 year old nulliparous woman was referred at 28 weeks of gestation because of severe pre-eclampsia in a dichorionic twin pregnancy conceived naturally. Her pregnancy was uneventful until 22 weeks of gestation, when a routine ultrasound scan revealed severe intrauterine growth restriction and reversed umbilical blood flow in one twin, while the other had normal development. At 28 weeks of gestation, the woman developed pre-eclampsia, with a blood pressure greater than 160/100 mmHg, proteinuria, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…87 This interpretation is consistent with previous reports of clinical resolution of preeclampsia following the death of the IUGR or hydropic fetus in twin pregnancies. [88][89][90][91][92] In conclusion, the study reported herein demonstrates that patients with TTTS had a significantly higher median maternal plasma concentration of s-Eng and sVEGFR-1 (both antiangiogenic factors), and a significantly lower median maternal plasma concentration of PlGF (an angiogenic factor) than those without TTTS. We propose that an anti-angiogenic state may be present in some cases of TTTS.…”
Section: Twin-to-twin Transfusion Syndrome: An Anti-angiogenic State?mentioning
confidence: 63%
“…87 This interpretation is consistent with previous reports of clinical resolution of preeclampsia following the death of the IUGR or hydropic fetus in twin pregnancies. [88][89][90][91][92] In conclusion, the study reported herein demonstrates that patients with TTTS had a significantly higher median maternal plasma concentration of s-Eng and sVEGFR-1 (both antiangiogenic factors), and a significantly lower median maternal plasma concentration of PlGF (an angiogenic factor) than those without TTTS. We propose that an anti-angiogenic state may be present in some cases of TTTS.…”
Section: Twin-to-twin Transfusion Syndrome: An Anti-angiogenic State?mentioning
confidence: 63%
“…We found two published cases (4,5) that describe the resolution of preeclampsia in twin pregnancies after the death of one fetus. Another case report shows resolution of preeclamptic symptoms after selective fetocide of one twin in a dichorionic twin pregnancy (6). A later reappearance of the preeclamptic symptoms in twins after the intrauterine death of one twin was (to our knowledge) never reported in the international literature.…”
Section: Discussionmentioning
confidence: 72%
“…As pre-eclampsia in some dichorionic twin gestations may be linked to the poor growth of one fetus, some authors have described selective feticide of the abnormal twin. 8,9 In these cases, selective feticide ultimately led to placental death, and the consequent resolution of pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%